Ride along : 2-movie collection [videorecording (DVD)] - Story, Tim; Brezner, Larry; Coolidge, Greg; Mantzoukas, Jason; Hay, Phil; Manfredi, Matt; Packer, Will; Alvarez, Matt; Lennertz, Christopher; Blanford, Larry; Amundsen, Mitchell, 1958-; Ice Cube (Musician); et al. (2017)
Ride along: Fast-talking security guard Ben joins his soon-to-be brother-in-law James on a 24-hour patrol of Atlanta in order to prove himself worthy of marrying Angela, James's sister.